Answer:
5/(y+5)
Explanation:
Perhaps you want the sum ...
![(3y)/(y^2+7y+10)+(2)/(y+2)\\\\=(3y)/((y+2)(y+5))+(2(y+5))/((y+2)(y+5))=(3y+2(y+5))/((y+2)(y+5))\\\\=(5y+10)/((y+2)(y+5))=(5(y+2))/((y+2)(y+5))=\boxed{(5)/(y+5)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pdpxxrnihh6zo3q5521jae1a3il0kcv37u.png)
_____
Comment on rational expressions
When writing ratios in plain text, it is imperative to put parentheses around numerators and denominators. (If the numerator is a product only, then parentheses are optional.)
Your expression might be properly written as ...
3y/(y^2 +7y +10) +2/(y+2)
As you have written it, it simplifies to ...
3(y/y)2 +7y +10 +2/y +2 = 3·2 +7y +2/y +12
= 7y +2/y +18
Please note, too, the exponentiation symbol (^).